DISIPLINER GURU PADA PROSES PEMBELAJARAN DALAM PERSPEKTIF QS. AL BAQARAH:44 - Al Ghifari; Indah puspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine teacher disciplinary conduct in the learning process based on the perspective of QS. Al-Baqarah: 44, which emphasizes the importance of consistency between preaching and practice of moral values. This research employed a descriptive qualitative method through literature review from various academic journals and articles. The findings reveal that teacher discipline extends beyond technical aspects such as attendance and administrative completeness. It encompasses moral integrity, exemplary behavior, communication skills, and the ability to design integrative curricula that combine religious and secular sciences. Teacher discipline also plays a crucial role in fostering a tolerant, relevant, and spiritually enriched educational environment. Thus, the implementation of discipline in teachers is a fundamental key to achieving meaningful and Qur’anic-based education.